Expulsion of dominant submucosal fibroids after uterine artery embolization - Radeleff, Boris; Eiers, Michael; Bellemann, Nadine; Ramsauer, Stefanie; Rimbach, Stefan; Kauczor, Hans-Ulrich; Richter, Götz Martin (European journal of radiology, 2010)
Purpose - Purpose of this study was to evaluate the frequency, probability, and factors associated with expulsion of submucosal fibroids after uterine artery embolization (UAE) in addition to the technical and clinical results at 1-year follow-up. - Materials and methods - We determined the preinterventional volume of each dominant submucosal fibroid using the commonly used ellipsoid formula and a 3D volumetry in the MRI to define a threshold value in milliliters that indicates the probability for a fibroid expulsion. Assessment of fibroid expulsion was done by MRI at 3-month intervals for a year. Assessment of clinical mid term success was achieved by applying questionnaires at 1-year follow-up. - Results - Technical success was observed in all 20 patients (mean age of 41.4±5.6 years; range: 29.2-51.1 years). Two (10%) minor and one (5%) major complications occurred. 10/20 dominant submucosal fibroids were completely expelled during the follow-up. Using 3D MRI volumetry the preinterventional mean volume of the later expelled fibroids was 56.8±57.0ml (range 2.3-198.0ml) and the mean volume of non-expelled fibroids was 123.8±147.3ml (range 24.0-531.8ml). This difference was statistically significant, but weak (p=0.0494). Fibroids with a volume equal or less than the threshold value (66.0ml) were 73% likely to be expelled and fibroids larger than 66.0ml were 78% likely not to be expelled. All 20 patients demonstrated a significant reduction in the fibroid related symptoms. - Conclusion - In our study the complication rate was low despite increased rates of fibroid expulsion (50%); simultaneously the rate of treatment satisfaction was very high. Patients with a dominant submucosal fibroid under 66.0ml should be informed about the probability of fibroid expulsion and the accompanying symptoms.
Online verfügbar 18. August 2009
Gesehen am 09.05.2023